2022
DOI: 10.4269/ajtmh.21-0515
|View full text |Cite
|
Sign up to set email alerts
|

A Mapping Review on the Uptake of the COVID-19 Vaccine among Adults in Africa Using the 5As Vaccine Taxonomy

Abstract: Uptake of a vaccine is complete if individuals are aware of the associated risks of the vaccine, accept the vaccine, and respond positively to the nudges (activation) to increase the uptake, and respond when the vaccine is made accessible and affordable. We mapped systematically the existing literature concerning the 5As—acceptability, accessibility, affordability, awareness, and activation—of COVID-19 vaccination among adults and, specifically, older adults (55 years and older) in Africa. We searched multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 92 publications
1
23
0
Order By: Relevance
“…A mapping review of COVID-19 vaccine uptake among Adults 55 years and older in Africa with the 5A model taxonomy found that acceptance was the most commonly researched aspect of vaccine uptake (85%), followed by accessibility (25%), awareness (19%), and affordability (7%). 153 Activation was examined in only one study as a factor affecting COVID-19 vaccine acceptance. The review concluded that more studies are needed to evaluate the impact of nudges (activation) to improve COVID-19 vaccine uptake in African nations.…”
Section: Models To Address Vaccine Hesitancymentioning
confidence: 99%
“…A mapping review of COVID-19 vaccine uptake among Adults 55 years and older in Africa with the 5A model taxonomy found that acceptance was the most commonly researched aspect of vaccine uptake (85%), followed by accessibility (25%), awareness (19%), and affordability (7%). 153 Activation was examined in only one study as a factor affecting COVID-19 vaccine acceptance. The review concluded that more studies are needed to evaluate the impact of nudges (activation) to improve COVID-19 vaccine uptake in African nations.…”
Section: Models To Address Vaccine Hesitancymentioning
confidence: 99%
“…A study (28)focusing Kenya indicated that understanding geographical access regarding to Covid-19 vaccination locations is key for successful planning of vaccination programmes. A study focusing Kenya, Uganda, Tanzania, and other countries noted that accessibility was based on location-distance to vaccination centers (29).…”
Section: Barriers To Uptake Of Vaccines Lack Of Access To Vaccinesmentioning
confidence: 99%
“…A study (32) focusing Kenya and other countries and another study (34) focusing Kisumu on Kenya reported concerns regarding vaccine safety and side effects. Similarly, a study (29) focusing Kenya, Uganda and Tanzania noted that safety concerns were still a barrier on vaccine uptake among adults.…”
Section: Fear Of Side Effectsmentioning
confidence: 99%
See 2 more Smart Citations